Strengthening disclosure regulations to increase market transparency and investment decisions: Evidence from the Vietnamese stock market - Hang, Nguyen Minh; Yen, Nguyen Ngoc (Edelweiss Applied Science and Technology, 2026)
Strengthening disclosure regulations to increase market transparency and investment decisions: Evidence from the Vietnamese stock market. Information disclosure plays a fundamental role in ensuring transparency and efficiency in financial markets. In emerging markets, where the legal framework and regulatory enforcement are still developing, the quality of corporate information disclosure is particularly important for mitigating information asymmetry and enhancing investor confidence. For the Vietnamese stock market, improving information disclosure practices has been recognized as a top priority to promote market transparency and sustainable capital market development. However, empirical evidence on the impact of information disclosure quality on investor perceptions and investment decisions in Vietnam remains limited. This study aims to examine the impact of information disclosure quality on market transparency, investor confidence, and investment decisions in the Vietnamese stock market. This study uses a quantitative approach, drawing on survey data collected from 326 individual investors and financial professionals participating in the Vietnamese stock market. Structural Equation Modeling (SEM) was applied to examine the relationships among information disclosure quality, market transparency, investor confidence, and investment decisions. Empirical results show that market transparency and investor confidence mediate the relationship between information disclosure quality and investment behavior. This study contributes to the existing literature by providing empirical evidence on the mechanisms linking information disclosure to investment decisions in emerging markets. The findings also offer important policy implications for regulators and listed companies in strengthening information disclosure practices, improving market transparency, and enhancing investor confidence in the Vietnamese stock market.